Biofilms in the dairy industry - Teh, Koon Hoong; Flint, Steve, 1955-; Brooks, John, 1947-; Knight, Geoff (Chichester, UK ; Hoboken, NJ : John Wiley & Sons, 2015)
In recent years, the formation and impacts of biofilms on dairy manufacturing have been studied extensively, from the effects of microbial enzymes produced during transportation of raw milk to the mechanisms of biofilm formation by thermophilic spore-forming bacteria. The dairy industry now has a better understanding of biofilms and of approaches that may be adopted to reduce the impacts that biofilms have on manufacturing efficiencies and the quality of dairy products. Biofilms in the Dairy Industry provides a comprehensive overview of biofilm-related issues facing the dairy sector. The book.
Introduction to biofilms: definition and basic concepts / Phil Bremer, Steve Flint, John Brooks and Jon Palmer -- Significance of bacterial attachment: a focus on the food industry / Jon Palmer, Brent Seale and Steve Flint -- The effect of milk composition on the development of biofilms / Steve Flint, Norshhaidah Mohd Jamaludin, Ben Somerton, Jon Palmer and John Brooks -- Overview of the problems resulting from biofilm contamination in the dairy industry / Brent Seale, Phil Bremer, Steve Flint, John Brooks and Jon Palmer -- Raw milk quality influenced by biofilms and the effect of biofilm growth on dairy product quality / Koon Hoong Teh, Steve Flint and Phil Bremer -- Thermoresistant streptococci / Steve Flint, John Brooks and Phil Bremer -- Thermophilic spore-forming bacilli in the dairy industry / Brent Seale, Sara Burgess, Steve Flint, John Brooks, Phil Bremer and Shanthi Parkar -- Biofilm contamination of ultrafiltration and reverse-osmosis plants / Xuemei Tang, Steve Flint, Rod Bennett, John Brooks and Siti Norbaizura Md Zain -- Pathogen contamination in dairy manufacturing environments / Shanthi Parkar, Steve Flint, Koon Hoong Teh, John Brooks and Phil Bremer -- Biofilm issues in dairy waste effluents / Michael Dixon, Steve Flint, Koon Hoong Teh and Kieran Mellow -- Biofilm modelling / John Brooks, Isabel Li and Robin Hankin -- Biofilm control in dairy manufacturing plants / Geoff Knight.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Biofilms; Dairy products industry; SCIENCE / Life Sciences / Biology; SCIENCE / Life Sciences / Microbiology; Biofilms; Dairy products industry; Biofilms; Dairy products industry; Dairy products; Electronic books